Generating Requirements Views: A Transformation-Driven Approach - Silva, Lyrene; Sampaio do Prado Leite, Julio (Electronic Communications of the EASST, 2007)
This paper reports the use of transformations based on XML to generate requirements views. A strategy to generate views is defined and scenarios and class diagrams are automatically created from a goal oriented model; the V-graph.